THE ROLE OF ACCOUNTING FOR THE SOCIAL RESPONSIBILITY OF ECONOMIC UNITS IN INCREASING THEIR ABILITY TO CONFRONT HEALTH CRISES – A SURVEY STUDY OF A SAMPLE OF WORKERS IN IRAQI TELECOMMUNICATIONS COMPANIES - Malik Ahmed Awad; Hamza Nahedh Al-Jumaili (Scholars Digest Publishing, 2024)
The idea of social responsibility for economic units results from economic units bearing part of the social burdens, and their role becomes more prominent and expands in disasters and economic crises. Therefore, they must bear a social responsibility to advance the interconnected pillars and strengthen them to overcome crises and achieve economic and social development at the local, national, regional and global levels. The social responsibility of economic units, in general, was built on a voluntary basis, following a policy that takes into account the extent to which economic units bear part of the burdens as a contribution to overcoming global crises, by working to improve the conditions of employees, their families, and the local community in exceptional circumstances, and based on the above, our research came to Measuring the impact of social responsibility accounting in raising companies’ ability to confront health crises, as the communications sector was chosen as a community for research and focusing on the main companies for this sector that operate in Iraq, which are (Asia Cell Company, Zain Iraq Company, Korek Company), and to achieve the goal of the study, it was Design a questionnaire form that is compatible with the research variables and present it to the employees of these companies to express their opinion on the extent to which the social responsibility adopted by their companies affects increasing their ability to confront the Corona crisis. The most important finding of the research is that paying attention to social responsibility factors increases their chances of success in confronting health crises and is the best evidence. The Corona pandemic, and it became clear to us through the results of our research that the most important factor that helped companies increase their ability to confront the Corona pandemic is analyzing and understanding the potential social and environmental risks that may arise as a result of the health crisis (Corona), in addition to paying attention to the factor of disclosure and transparency, as the company worked to enhance this aspect. Which created good confidence among the public and investors. The other factor, which is no less important than what was mentioned and recorded a high degree of support from company employees, is the factor of interest in the social aspect of society, as companies participated in social and health projects and provided the support that society needs during the crisis (Corona pandemic). Which enhanced the building of relationships between society and companies. Our research recommends working continuously to develop corporate social responsibility in order to be able to bear the burdens of health crises because they are part of the community to which they belong, and giving the accounting side greater priority to disclose community expenditures and include them in the main lists, and that the economic units that provided community services at the time The (Covid-19) crisis has gained a better reputation than companies that did not play a positive role in overcoming the crisis.
Keywords: social responsibility accounting, health crises, Corona pandemic, Iraqi telecommunications companies.